Proteome wide reduction in AGE modification in streptozotocin induced diabetic mice by hydralazine mediated transglycation - Kesavan, Suresh K.; Bhat, Shweta; Golegaonkar, Sandeep B.; Jagadeeshaprasad, Mashanipalya G.; Deshmukh, Arati B.; Patil, Harshal S.; Bhosale, Santosh D.; Shaikh, Mahemud L.; Thulasiram, Hirekodathakallu V.; Boppana, Ramanamurthy; Kulkarni, Mahesh J. (Scientific Reports, 2013)
The non-enzymatic reaction between glucose and protein can be chemically reversed by transglycation. Here we report the transglycation activity of hydralazine using a newly developed MALDI-TOF-MS based assay. Hydralazine mediated transglycation of HbA1c, plasma proteins and kidney proteins was demonstrated in streptozotocin (STZ) induced diabetic mice, as evidenced by decrease in protein glycation, as well as presence of hydralazine-glucose conjugate in urine of diabetic mice treated with hydralazine. Hydralazine down regulated the expression of Receptor for Advanced Glycation End products (RAGE), NADPH oxidase (NOX), and super oxide dismutase (SOD). These findings will provide a new dimension for developing intervention strategies for the treatment of glycation associated diseases such as diabetes complications, atherosclerosis, and aging.

Immune response to chemically modified proteome - Bhat, Shweta; Mary, Sheon; Banarjee, Reema; Giri, Ashok P.; Kulkarni, Mahesh J. (Proteomics Clinical Applications, 2014)
Both enzymatic and nonenzymatic PTMs of proteins involve chemical modifications. Some of these modifications are prerequisite for the normal functioning of cell, while other chemical modifications render the proteins as neo-self antigens, which are recognized as non-self leading to aberrant cellular and humoral immune responses. However, these modifications could be a secondary effect of autoimmune diseases, as in the case of type I diabetes, hyperglycemia leads to protein glycation. The enigma of chemical modifications and immune response is akin to the chick-and-egg paradox. Nevertheless, chemical modifications regulate immune response. In some of the well-known autoimmune diseases such as rheumatoid arthritis, systemic lupus erythematosus, and multiple sclerosis, chemically modified proteins act as autoantigens forming immune complexes. In some instances, chemical modifications are also involved in regulating immune response during pathogen infection. Further, the usefulness of proteomic analysis of immune complexes is briefly discussed.
Keywords: Autoantibody; Autoimmune diseases; Immune complex; Immunoproteomics; PTMs

Development of diagnostic fragment ion library for glycated peptides of human serum albumin: targeted quantification in prediabetic, diabetic, and microalbuminuria plasma by parallel reaction monitoring, SWATH, and MSE - Korwar, Arvind M.; Vannuruswamy, Garikapati; Jagadeeshaprasad, Mashanipalya G.; Jayaramaiah, Ramesha H.; Bhat, Shweta; Regin, Bhaskaran S.; Ramaswamy, Sureshkumar; Giri, Ashok P.; Mohan, Viswanathan; Balasubramanyam, Muthuswamy; Kulkarni, Mahesh J. (Molecular & Cellular Proteomics, 2015)
Human serum albumin is one of the most abundant plasma proteins that readily undergoes glycation, thus glycated albumin has been suggested as an additional marker for monitoring glycemic status. Hitherto, only Amadori-modified peptides of albumin were quantified. In this study, we report the construction of fragment ion library for Amadori-modified lysine (AML), N(epsilon)-(carboxymethyl) lysine (CML)-, and N(epsilon)-(carboxyethyl) lysine (CEL)-modified peptides of the corresponding synthetically modified albumin using high resolution accurate mass spectrometry (HR/AM). The glycated peptides were manually inspected and validated for their modification. Further, the fragment ion library was used for quantification of glycated peptides of albumin in the context of diabetes. Targeted Sequential Window Acquisition of all THeoretical Mass Spectra (SWATH) analysis in pooled plasma samples of control, prediabetes, diabetes, and microalbuminuria, has led to identification and quantification of 13 glycated peptides comprised of four AML, seven CML, and two CEL modifications, representing nine lysine sites of albumin. Five lysine sites namely K549, K438, K490, K88, and K375, were observed to be highly sensitive for glycation modification as their respective m/z showed maximum fold change and had both AML and CML modifications. Thus, peptides involving these lysine sites could be potential novel markers to assess the degree of glycation in diabetes.

Molecules with O-acetyl group protect protein glycation by acetylating lysine residues - Vannuruswamy, Garikapati; Jagadeeshaprasad, Mashanipalya G.; Kashinath, K.; Kesavan, Suresh K.; Bhat, Shweta; Korwar, Arvind M.; Chougale, Ashok D.; Boppana, Ramanamurthy; Reddy, D. Srinivasa; Kulkarni, Mahesh J. (RSC Advances, 2016)
Pharmaceutical intervention for reduction of advanced glycation end products (AGEs) is considered as a therapeutic strategy to attenuate the pathogenesis of diabetes. Many molecules have been reported to possess antiglycation activity, one such example is acetylsalicylic acid (aspirin). It protects proteins from glycation by acetylating the lysine residues. Therefore, in this study we have synthesized and screened molecules containing free N-acetyl, O-acetyl and acetophenone groups. All the selected molecules in this study showed glycation inhibition but interestingly, only molecules with O-acetyl but not N-acetyl and acetophenone groups were capable of acetylating lysine residue. Furthermore, we have demonstrated that pre-acetylation or aspirin treatment prior to the induction of diabetes helps in reducing HbA1c and AGE formation in the streptozotocin induced diabetic mice. Hence pre-acetylation may have an additional therapeutic efficacy of reducing AGE levels in vivo. Incorporation of O-acetyl group into anti-diabetic molecules could be a useful strategy, as it may have an additive effect in reducing AGEs. Identification of such novel acetylating agents represents a new area in the drug discovery process.

Proteomic insight reveals elevated levels of albumin in circulating immunecomplexes in diabetic plasma - Bhat, Shweta; Jagadeeshaprasad, Mashanipalya G.; Patil, Yugendra R.; Shaikh, Mahemud L.; Regin, Bhaskaran S.; Mohan, Viswanathan; Giri, Ashok P.; Balasubramanyam, Muthuswamy; Boppana, Ramanamurthy; Kulkarni, Mahesh J. (Molecular & Cellular Proteomics, 2016)
A Hyperglycemic condition in diabetes promotes formation of advanced glycation end products, which are known to elicit immune response and form complexes with immunoglobulins called circulating immune complexes. To investigate the involvement of advanced glycation end product (AGE)-modified proteins in the elicitation of an immune response, circulating immune complexes were isolated and proteins associated were identified and characterized. Label-free-based mass spectrometric analysis of circulating immune complexes in clinical plasma of prediabetic, newly diagnosed diabetes, and diabetic microalbuminurea revealed elevated levels of serum albumin in the circulating immune complexes, which were also observed to be AGE modified. Further, to examine the role of glycation, circulating immune complexeswere analyzed in the streptozotocin-induced diabetic mice treated with or without aminoguanidine, a prototype glycation inhibitor. Mass spectrometric analysis of circulating immune complexes showed elevated levels of serum albumin in plasma from diabetic mice over that of control animals. Aminoguanidine-treated diabetic mice displayed decreased AGE modification of plasma albumin, accompanied by a reduced level of albumin in the circulating immune complexes. In addition, elevated levels of proinflammatory cytokines such as IL-1b, IL-2, and TNF-alpha were observed in diabetes, which were reduced with aminoguanidine treatment, suggesting the involvement of glycation in the immune response.

Abundance matters: role of albumin in diabetes, a proteomics perspective - Bhat, Shweta; Jagadeeshaprasad, Mashanipalya G.; Venkatasubramani, Vinashya; Kulkarni, Mahesh J. (Expert Review of Proteomics, 2017)
Introduction: Human serum albumin (HSA) is a multifaceted protein with vital physiological functions. It is the most abundant plasma protein with inherent capability to bind to diverse ligands, and thus susceptible to various post-translational modifications (PTMs) which alter its structure and functions. One such PTM is glycation, a non-enzymatic reaction between reducing sugar and protein leading to formation of heterogeneous advanced glycation end products (AGEs). Glycated albumin (GA) concentration increases significantly in diabetes and is implicated in development of secondary complications. Areas covered: In this review, we discuss in depth formation of GA and its consequences, approaches used for characterization and quantification of GA, milestones in GA proteomics, clinical relevance of GA as a biomarker, significance of maintaining abundant levels of albumin and future perspectives. Expert commentary: Elevated GA levels are associated with development of insulin resistance as well as secondary complications, in healthy and diabetic individuals respectively. Mass spectrometry (MS) based approaches aid in precise characterization and quantification of GA including early and advanced glycated peptides, which can be useful in prediction of the disease status. Thus GA has evolved to be one of the best candidates in the pursuit of diagnostic markers for prediction of prediabetes and diabetic complications.